Effect of Trehalose on Cryopreservation of Hariana Bull Spermatozoa - Kumar, Gyanesh; Yadav, Dileep Kumar; Saxena, Atul; Sachan, Vikas; Kumar, Anuj; Swain, Dilip Kumar; Yadav, Brijesh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present experiment was designed to study the effect of supplementation of Trehalose on freezability and antioxidant activity of Hariana bull semen. Semen samples were diluted in TFYG extender containing different concentrations of Trehalose (10mM, 30mM & 50mM). The control samples were extended with TFYG alone.  Results clearly indicated that, 30 mM Trehalose group had significantly (P
Keywords: Antioxidant; Cryopreservation; Freezability; Hariana bull; Trehalose